Stratifikasi Sosial dalam Budaya Bugis: Eksistensi Gelar Andi dalam Masyarakat Modern - Yunita Mahrany; Andi Triwenni Wulandari; Muhammad Rasyid Ridha (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
This study aims to examine the existence of the title "Andi" in the context of social stratification of Bugis society and its relevance in the modern era. The title Andi is a symbol of nobility that has been passed down from generation to generation and has an important role in the traditional social structure of the Bugis. Through a qualitative-descriptive approach, this study explores the symbolic meaning of the title, its influence on social interactions, perceptions of it in contemporary marriage practices, differences in views between generations, and strategies for preserving it amidst the current of modernization. The results of the study show that although traditional values are beginning to shift, the title Andi still has a strong social and cultural meaning for most Bugis people. The older generation tends to maintain the values of honor and status attached to the title, while the younger generation shows a more flexible tendency in interpreting the symbol. This study recommends preservation efforts based on cultural education, integration of local values in education, and strengthening identity through digital media. These findings show that the title Andi is not merely a symbolic identity, but also an important part of cultural heritage that can transform over time without losing its essence.